ANALISIS EFEKTIVITAS, EFISIENSI, DAN KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PAD KABUPATEN BLORA TAHUN 2009-2013 - Ayu Puspitasari, Elfayang Rizky; Rohman, Abdul (Diponegoro Journal of Accounting, 2014)
This research is purpose to know (1) how the effectiveness of local taxes at Kabupaten Blora through 2009-2013. (2) how the effectiveness of local retribution at Kabupaten Blora through 2009-2013. (3) how the efficiency of local taxes at Kabupaten Blora through 2009-2013. (4) how the efficiency of local retribution at Kabupaten Blora through 2009-2013. (5) how the contribution of local taxes against original regional income at Kabupaten Blora through 2009-2013. (6) how the contribution of local retribution against original regional income at Kabupaten Blora through 2009-2013.This research used quantitative descriptive method. The techniques of data collection are documentation and interview. The data used: the potential of local taxes and local retribution, the realization of local tax, local retribution, and regional income. The data were analyzed using the effectiveness analysis, the efficiency analysis, the contribution analysis, and the different t-test analysis.The results of this research are: (1) category of the  effectiveness rate for local taxes and local retribution through 2009-2013 are very effective. (2) the efficiency rate for local taxes and local retribution from 2009 until 2013 overall in efficient level. (3) the contribution of local taxes againt original regional income Kabupaten Blora from 2009 until 2013 doesn’t have contribution. However, the level of contribution ratio tends to rise. (4) the contribution of local retribution againt original regional income Kabupaten Blora through 2009-2013 being contributed but the contribution ratio tends to falling down each year. (5) the different t-test analysis for the effectiveness and efficiency of local taxes and local retribution showed no difference. Whereas for the contribution of local taxes and local retribution shows the difference between both.